Changes in common ownership of German companies - Jo Seldeslachts; Melissa Newham; Albert Banal-Estanol (DIW Economic Bulletin, 2017)
Ownership of publicly listed German companies has undergone significant changes in recent years. The aim of this report is to document these trends since 2007 and analyze the extent to which firms that compete in the same product market are owned by the same investors, which is known as common ownership. We show that some large foreign institutional investors have overtaken domestic investors and now occupy the top spots. This is true both in terms of value and the number of blockholdings, i.e. large blocks of shares.In addition, there has been an increase in ownership concentration overall. That said, private and governmental investors with few but large holdings, still own more than half of German equity. Using two leading industries, the chemical and car industries, we show that ownership trends and levels of common ownership can be very different across industries. While it is unclear a priori what common ownership implies for competition, innovation, and consumer welfare, markets that show more common ownership, such as the chemical sector, deserve more attention from policy makers, regulators, and academics alike.
Keywords: D43; G23; K21; L62; L65; 330; institutional investors; common ownership; German markets; innovation; competition; antitrust